LOGAM DAN PLASTIK DOMINAN PADA SAMPAH LAUT DARI JENIS MESO DAN MAKRO - Yusra . (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2022)
Marine debris is all forms of solid objects that are disposed of intentionally or unintentionally into the marine environment. Research on the type, composition, amount, and density of marine debris that washed up on Air Manis Beach and Pasir Jambak Beach has never been done. The purpose of this study was to determine the source, amount, type and density of marine debris found at Air Manis Beach and Pasir Jambak Beach, Padang City. The research was conducted from March to July 2022. The method used to collect waste was using the line transect method, the location determination was carried out intentionally according to research needs (purposive sampling). All waste obtained during the study was grouped by type, amount and size. Based on the research, it is known that the garbage stranded on the two beaches comes from the river, the activities of residents around the location, fishing activities and visiting tourists. It was found that there were 36232.24 grams of waste consisting of 36195.4 grams of macro waste and 36.84 grams of meso waste. Macro waste with the highest percentage was found in plastic waste (86.84%), and for meso-sized waste was found in metallic waste (72.27%). The density of marine debris at Air Sweet Beach and Pasir Jambak Beach is 23.36 pieces/m2 for macro waste and 4.2 pieces/m2 for meso waste.